Sabrina - Benedek, Barbara; Rayfiel, David; Rudin, Scott, 1958-; Pollack, Sydney, 1934-2008; Ford, Harrison, 1942-; Ormond, Julia; Kinnear, Greg, 1963-; Marchand, Nancy, 1928-2000; Wood, John, 1930-2011; Williams, John, 1932-; Bergman, Alan; Bergman, Marilyn; et al. (Hollywood, California : Paramount Pictures, 2001)
Sabrina, the naive daughter of the chauffeur for an immensely wealthy family, is obsessed with David, the family's younger son. When Sabrina returns to Long Island from Paris as a sophisticated young woman, she begins a romance with David, who has meanwhile become engaged to the daughter of a wealthy family. This new romance threatens the business interests of Linus, the older son, so he pretends to court Sabrina in order to woo her away from David, but ends up falling in love with her himself
Originally released as a motion picture in 1995
Based on the 1954 film written by Billy Wilder, Samuel Taylor, and Ernest Lehman, from the play by Samuel Taylor
Music by John Williams ; original songs by John Williams and Alan & Marilyn Bergman ; edited by Frederic Steinkamp ; production designer, Brian Morre ; director of photography, Giuseppe Rotunno
Harrison Ford, Julia Ormond, Greg Kinnear, Nancy Marchand, John Wood
Rated PG; for some mild language
DVD; widescreen presentation enhanced for 16x9 TVS; NTSC, region 1; Dolby Digital 5.1 Surround, Dolby Digital 2.0 Surround, Dolby Stereo
Keywords: Man-woman relationships -- Drama; Triangles (Interpersonal relations) -- Drama; Brothers -- Drama; Rich people -- Drama; Social classes -- Drama; Brothers; Man-woman relationships; Rich people; Social classes; Triangles (Interpersonal relations); Long Island (N.Y.) -- Drama; New York (State) -- Long Island; Long Island (N.Y.) -- Drama; Romantic comedy films; Romance films; Comedy films; Film remakes; Film adaptations; Fiction films; Feature films; Video recordings for the hearing impaired; Romantic comedy films; Comedy films; Feature films; Video recordings for the hearing impaired; Films for the hearing impaired; Feature films; Films for the hearing impaired